STUDY ON THE MORPHOMETRIC AND MERISTIC CHARACTERISTICS OF SPLENDID SILVER BELLY- LEIOGNATHUS SPLENDENS (CUVIER) FROM BOMBAY COAST - GULATI, DEEPAK; ACHARYA, P. (Journal of Indian Fisheries Association, 2015)
Ten morphometric and six meristic characters of Leiognathus splendens.(Cuvier) of Bombay Coast have been studied sexwise. Regression and sexwisedifference if any between the compared morphometirc characteristics havebeen worked out. Range, mode, standard deviation, co-efficient of variationof 6 meristic characters have been analysed. The was no significant differencebetween the sexes in morphometric and any deviation in the meristiccharacters.Keywords : Silves bellies, Morphometry, Bombay Coast.